Serum human epididymis protein 4 is associated with disease severity in patients with IgA nephropathy - Luo, Hou-Long; He, Chen; Xue, Hao; Li, Mingyang; Ji, Ling; Xia, Yong (Clinical biochemistry, 2024)
•Serum HE4 levels were significantly elevated in patients with IgAN.•Elevated serum HE4 levels are closely related to diverse clinical parameters and kidney function indicators.•HE4-positive patients exhibited poorer renal function.•The greater the pathology score, the higher the serum HE4 level in patients with IgAN. Human epididymis protein 4 (HE4) is a promising tumor biomarker primarily utilized for the detection of ovarian cancer. However, its potential as a novel diagnostic indicator for immunoglobulin A nephropathy (IgAN) remains unknown. The objective of this study was to investigate the feasibility of serum HE4 as a novel biomarker for patients with IgAN. This study enrolled a total of 89 hospitalized patients with IgAN at Peking University Shenzhen Hospital between July 2020 and December 2022, along with 60 healthy control subjects matched for sex and age without evidence of comorbidities. Serum HE4 levels were measured using the Abbott Alinity automated immune analyzer, and the correlation between serum HE4 levels and biochemical markers of renal damage as well as clinicopathologic features in IgAN patients were analyzed. In this study, serum HE4 levels were significantly elevated in patients with IgAN compared to healthy controls (116.43 ± 103.61 pmol/L vs. 35.57 ± 9.33 pmol/L, p < 0.001). There was a positive correlation between serum HE4 levels and blood urea nitrogen (r = 0.58, p < 0.001), creatinine (r = 0.73, p < 0.001), cystatin C (r = 0.82, p < 0.001), β2-microglobulin (r = 0.77, p < 0.001), α1-microglobulin (r = 0.75, p < 0.001), and glomerulosclerosis ratio (r = 0.56, p < 0.001). Conversely, a negative correlation was observed between serum HE4 levels and hemoglobin (r = -0.42, p < 0.001), albumin (r = -0.44, p < 0.001) and estimated glomerular filtration rate (eGFR) (r = -0.83, p < 0.001). In HE4+ IgAN patients, a higher glomerulosclerosis ratio (p < 0.01) and lower eGFR levels (p < 0.001) were observed compared to HE4- patients. Furthermore, patients with higher pathological classification grade also had higher serum HE4 levels. Serum HE4 levels were significantly associated with both renal function and the pathological classification of patients with IgAN, indicating that HE4 may serve as a promising biomarker for assessing the severity of IgAN.